An Implementation of Storytelling Technique to Improve Students’ Speaking Ability - Huda, Rahmat; Parapat, Lili Herawati; Wardhani, Anggi Tri (English Education : English Journal for Teaching and Learning, 2023)
The research’s aims explained speaking problems and speaking ability of students by implementing Story Telling Technique. This research used qualitative research method and 14 students of the Grade X of SMA Negeri 3 Padang Sidempuan. Instrument in collecting the data were interview and test. The finding of the research shows; Firstly, students’ problems in speaking before implementing the technique were: limited vocabulary, confused to pronounce the correct words, and difficult to understand what the speakers were said. Secondly, after implementing the technique, the students’ new vocabulary enrichment, had more experienced how to pronounce words correctly, and easier to understand what the speaker were saying.